2023
DOI: 10.1007/s00431-023-05131-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing rights-based standards for children having tests, treatments, examinations and interventions: using a collaborative, multi-phased, multi-method and multi-stakeholder approach to build consensus

Lucy Bray,
Bernie Carter,
Joann Kiernan
et al.

Abstract: Children continue to experience harm when undergoing clinical procedures despite increased evidence of the need to improve the provision of child-centred care. The international ISupport collaboration aimed to develop standards to outline and explain good procedural practice and the rights of children within the context of a clinical procedure. The rights-based standards for children undergoing tests, treatments, investigations, examinations and interventions were developed using an iterative, multi-phased, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Preparing children for needle-related procedures and supporting them before, during and after has been shown to have clear benefits (Dalley and McMurtry, 2016; Uman et al, 2008). Children have better experiences and outcomes if they are prepared for an upcoming procedure, are cared for in an environment that is comfortable, receive pain management and distraction techniques and are coached through the procedure by a calm adult (Bray et al, 2023; Taddio et al, 2009). By providing meaningful information and supporting children to develop positive coping mechanisms and self-regulation, children experience less anxiety and less pain and have shorter appointment times (Orenius et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Preparing children for needle-related procedures and supporting them before, during and after has been shown to have clear benefits (Dalley and McMurtry, 2016; Uman et al, 2008). Children have better experiences and outcomes if they are prepared for an upcoming procedure, are cared for in an environment that is comfortable, receive pain management and distraction techniques and are coached through the procedure by a calm adult (Bray et al, 2023; Taddio et al, 2009). By providing meaningful information and supporting children to develop positive coping mechanisms and self-regulation, children experience less anxiety and less pain and have shorter appointment times (Orenius et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, commitments to personalised care, patient choice, and shared decision making are embedded in the NHS Long Term Plan (2019). Implementing these practices in paediatric care requires recognition and competence around children's rights and children's agency, which must include competence around play.The emphasis that children place on their sense of choice, ownership, and confidence related to play in a hospital environment speaks to the importance of systematically attending to and including their perspectives on the role and value of play in their health care Bray et al (2023). reported that children and young people find it hard to share their views and have them listened to in health care settings, and that staff lack necessary training to deliver child-centred preparation and information.…”
mentioning
confidence: 99%